Exposure and power of food marketing to children in Portugal, through TV, radio and websites – a pilot study - Cardoso, Rafael (2017)
INTRODUCTION: Marketing of foods high in fat, salt and sugar (HFSS) has been idenDfied as a significant risk factor for childhood obesity and for the development of diet-related noncommunicable diseases. The World Health OrganizaDon (WHO) has been providing guidance to Member States to reduce food marketing pressure on children. Portugal has adopted legislation early 2016 to restrict food marketing to children in a series of platorms, ranging from school premises, to TV channels, Radio stations and Internet. EvaluaDng and monitoring its implementation is pivotal to ensure that effective action is taken. OBJECTIVE: To conduct a pilot study to idenDfy the most frequently used TV channels, radio stations and websites among children; To assess the marketiong of HFSS foods on TV and Radio using the WHO Regional Office for Europe nutrient profile model.